2023
DOI: 10.1186/s41935-023-00329-2
|View full text |Cite
|
Sign up to set email alerts
|

Study of twenty non-metric dental crown traits using ASUDAS system in NCR (India) population

Abstract: Background The non-metric dental crown traits (NDCT) can vary within and between the geo-populations. These play a critical role in the ethnicity determination and help in identification of an individual. A commonly used system for scoring these dental traits is “Arizona State University Dental Anthropology System” (ASUDAS). Aim and objectives Our study aims to evaluate the frequency trend of twenty NDCT traits in the India, National Capital Region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…Their research revealed that males and females had slightly larger proportions of premolar accessory cusps in first and second premolars, respectively. 3 These patterns show the shape of the premolars and are independent of tooth size. The present study explores the change in the shape of the premolars using landmark based morphometric evaluation.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Their research revealed that males and females had slightly larger proportions of premolar accessory cusps in first and second premolars, respectively. 3 These patterns show the shape of the premolars and are independent of tooth size. The present study explores the change in the shape of the premolars using landmark based morphometric evaluation.…”
Section: Introductionmentioning
confidence: 96%
“…However tooth are less influenced by hormones (Oettlé et al, 2009). In a study byGuatelli-Steinberg et al (2008) on seven different populations, they found no significant association of sex hormone concentrations post-birth and tooth patterning 3. However,Ribeiro D et al (2013) have demonstrated a significant role of intrauterine testosterone levels in dental development and size 4.…”
mentioning
confidence: 97%